Extraction of cooper from aqueous solutions using iron powder materials - Mironov, Victor A.; Shishkin, Andrei Y.; Polyakov, Aliaksandr V.; Treijs, Juris K. (Journal of the Belarusian State University. Ecology, 2018)
The method of purification of wastewater containing copper with the use of iron powders is considered and investigated. A new technology for the rapid introduction, dispersion and mixing of iron powders with copper ions (CuCO4) contained in wastewater (pH = 2,0 / 3,0), formed during the execution of a number of technological processes, is proposed. The study used a high-speed dispersant-cavitator. A comparison is made of its operation with a standard propeller-type laboratory mixing plant to evaluate the effect of the parameters of mixing devices of various types that are related to the efficiency of the copper extraction process. The use of a dispersant-cavitator in the extraction of copper proved to be more effective than the propeller-type mixing device. The degree of recovery of Co2 + increased by 88%, and the duration of the process was reduced by 30 %.